New Phenotypes of Potato Co-induced by Mismatch Repair Deficiency and Somatic Hybridization - Rakosy-Tican, Elena; Lörincz-Besenyei, Enikö; Molnár, Imola; Thieme, Ramona; Hartung, Frank; Sprink, Thorben; Antonova, Olga; Famelaer, Ivan; Angenon, Geert; Aurori, Adriana (Frontiers in Plant Science, 2019)
Plants being sessile organisms need a very efficient DNA repair system against external or internal mutagens. Mismatch repair (MMR) is one of the guard systems that maintains genome integrity and prevents homeologous recombination. In all eukaryotes mismatches are recognized by evolutionary conserved MSH proteins often acting as heterodimers, the constant component being MSH2. Changes affecting MSH2 gene function may induce a 'mutator' phenotype and microsatellite instability, as it was demonstrated in MSH2 knock-out and silenced lines of Arabidopsis thaliana. The goal of our study was to screen for 'mutator' phenotypes in somatic hybrids between potato cvs. 'Delikat' and 'Désirée' and MMR deficient Solanum chacoense transformed previously with antisense (AS) or dominant negative mutant (DN) AtMSH2 genes. The results demonstrate that in the first generation of fusion hybrids diverse morphological abnormalities are caused by uniparental MMR deficiency; these mutant phenotypes include: dwarf or gigantic plants; bushiness; curled, small, large or abnormal leaves; a deterioration of chloroplast structure; small deep-purple tubers and early dehiscent flowers. 40 % of the viable somatic hybrids planted in a greenhouse, (10 out of 25 genotypes), displayed a mutant phenotype accompanied by microsatellite instability (MSI). The majority of the hybrids with 'mutator' phenotypes developed roots on kanamycin containing media sustaining the presence of selectable marker gene nptII, from the initial constructs. This report shows for the first time the use of MMR deficiency combined with somatic hybridization to induce new phenotypes in plants and support the role of mismatch repair deficiency in increasing introgressions between the two related species.